2014
DOI: 10.1016/j.humpath.2014.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of major cancer resection specimens with virtual slides: impact of a novel digital pathology workstation

Abstract: Summary:Digital pathology promises a number of benefits in efficiency in surgical pathology, yet the longer time required to review a virtual slide than a glass slide currently represents a significant barrier to the routine use of digital pathology. We aimed to create a novel workstation that enables pathologists to view a case as quickly as on the conventional microscope. The Leeds Virtual Microscope (LVM) was evaluated using a mixed factorial experimental design. Twelve consultant pathologists took part, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 12 publications
(15 reference statements)
1
34
0
1
Order By: Relevance
“…From the United Kingdom, a small study (n = 12) evaluated the feasibility of using VSs in the diagnosis of major cancer resection specimen to improve efficiency in surgical pathology. 120 VM was used for real-time rendering of diagnoses. ''Total time taken and diagnostic confidence were similar for the microscope and the virtual microscope, as was the mean slide viewing time.''…”
Section: Telepathology Evidence: Feasibility and Acceptancementioning
confidence: 99%
“…From the United Kingdom, a small study (n = 12) evaluated the feasibility of using VSs in the diagnosis of major cancer resection specimen to improve efficiency in surgical pathology. 120 VM was used for real-time rendering of diagnoses. ''Total time taken and diagnostic confidence were similar for the microscope and the virtual microscope, as was the mean slide viewing time.''…”
Section: Telepathology Evidence: Feasibility and Acceptancementioning
confidence: 99%
“…Indeed, most pathologists feel that more time is required to make a diagnosis with WSI. However, some studies have shown that although diagnosis with WSI is initially more time-consuming, this time quickly decreases as pathologists become familiar with the use of the WSI viewer [30,31,32,33,34,35]. Thus, there is a learning curve in the use of WSI and the time required for making a diagnosis, and a recent study conducted at our institution confirmed that the diagnostic performance improved with practice [36].…”
Section: Advantages and Challenges Of Wsi For Routine Diagnosismentioning
confidence: 94%
“…It was concluded that most of the observed inefficiency was due to a combination of several factors, including: (i) the smaller field of view afforded by the digital slide system, (ii) issues with the design of the software used for viewing the slides and (iii) a lack of experience and training using digital slides with the participants. The first two of these issues were addressed in our subsequent work, which found that using higher‐resolution displays and moving the image pixels more quickly could improve pathologist efficiency with digital slides to the point that time to diagnosis could be equivalent with the appropriate systems . Subsequent commercial digital pathology systems have placed greater emphasis on performance and usability.…”
Section: Acceptance By Pathologistsmentioning
confidence: 99%